2010
DOI: 10.1073/pnas.1012820107
|View full text |Cite
|
Sign up to set email alerts
|

Structural space of protein–protein interfaces is degenerate, close to complete, and highly connected

Abstract: At the heart of protein-protein interactions are protein-protein interfaces where the direct physical interactions occur. By developing and applying an efficient structural alignment method, we study the structural similarity of representative protein-protein interfaces involving interactions between dimers. Even without structural similarity between individual monomers that form dimeric complexes, ∼90% of native interfaces have a close structural neighbor with similar backbone C α geometry and interfacial con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
134
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 34 publications
4
134
0
1
Order By: Relevance
“…The sequence similarity score between the HI of query "i" and its template is calculated using the following equation: (9) in which N intf is the total number of amino acids in the HI of the query and s j is the similarity score between the amino acid " j" in the query and the corresponding amino acid in the HI of the template " j ′ ." The value of s j equals one or zero if the BLOSUM62 50 element for jj ′ is greater than zero or less than or equal to zero, respectively.…”
Section: H Sequence Similarity Calculationmentioning
confidence: 99%
“…The sequence similarity score between the HI of query "i" and its template is calculated using the following equation: (9) in which N intf is the total number of amino acids in the HI of the query and s j is the similarity score between the amino acid " j" in the query and the corresponding amino acid in the HI of the template " j ′ ." The value of s j equals one or zero if the BLOSUM62 50 element for jj ′ is greater than zero or less than or equal to zero, respectively.…”
Section: H Sequence Similarity Calculationmentioning
confidence: 99%
“…Protein interfaces are usually large, with a buried solvent accessible area of over 1;000 Å 2 (3). With the exception of intertwined interface structures, most protein interfaces have planar shapes (4,9,10). Although there are in principle millions of ways of forming protein-protein interfaces, a recent study has revealed that the structural space of protein interfaces is surprisingly small, primarily attributed to limited ways of protein secondary structural packing and the flatness of interfaces (10).…”
mentioning
confidence: 99%
“…Artificial protein-protein interfaces were extracted from previously built artificial protein complexes (10). These artificial complexes were originally taken from a library of polyvaline structures generated with the protein structure prediction package TASSER (40).…”
mentioning
confidence: 99%
See 2 more Smart Citations